2018
DOI: 10.1016/j.rbms.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

A historical argument for regulatory failure in the case of Primodos and other hormone pregnancy tests

Abstract: The drug Primodos and other hormone pregnancy tests (HPTs) remained on the British market for about a decade after they were first implicated, in 1967, as a possible cause of birth defects. In November 2017, an expert working group (EWG) set up by the Medicines and Healthcare Products Regulatory Agency (MHRA) concluded against such an association. However, it was explicitly ‘not within the remit of the EWG to make formal conclusions or recommendations on the historical system or regulatory failures’, a situati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Increased gestational exposure to estrogens is associated with developmental defects of the reproductive system in both male and female offspring, tumour development and subfertility in adult life 4 . Likewise, oral hormone pregnancy tests (HPTs), such as Primodos, containing ethinylestradiol and high doses of synthetic progesterone, available from 1958 to 1978, were first implicated in 1967 as a possible cause of birth defects 5 , 6 . Recent meta-analysis concluded that HPTs were associated with a 40% increased risk of congenital malformations 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Increased gestational exposure to estrogens is associated with developmental defects of the reproductive system in both male and female offspring, tumour development and subfertility in adult life 4 . Likewise, oral hormone pregnancy tests (HPTs), such as Primodos, containing ethinylestradiol and high doses of synthetic progesterone, available from 1958 to 1978, were first implicated in 1967 as a possible cause of birth defects 5 , 6 . Recent meta-analysis concluded that HPTs were associated with a 40% increased risk of congenital malformations 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Hormone pregnancy tests, sodium valproate, and pelvic mesh have been the subject of regulatory action in the UK and elsewhere. The tests were withdrawn in 1979, 11 years after concerns first emerged 2. Sodium valproate, now also used as a psychiatric medication, is the subject of warnings and voluntary restrictions for women of childbearing age, although, as the report documents, it is surprisingly difficult to get this critical information to either patients or doctors 34.…”
mentioning
confidence: 99%
“…Oral hormone pregnancy tests (HPTs), such as Primodos (known as Duogynon in Germany), were available as injections from 1950 and in tablet form in the UK from 1956 onwards, before the modern forms of urine pregnancy tests became available 1 . Oral HPTs contained ethinylestradiol and large doses of norethisterone (synthetic forms of estrogen and progesterone respectively), the latter in much larger amounts than those included in current combined oral contraceptives (see Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…( Supplementary File 1) Warnings about HPTs in pregnancy first emerged in 1956: 4 accumulating concerns over an increased risk of malformations led to their withdrawal in a number of countries at different times. Norway cancelled the indication in pregnancy for HPTs in 1970; when the UK did so in 1978, the manufacturers of Primodos, Schering AG (taken over by Bayer AG in 2008), voluntarily stopped marketing the product; in Germany, Duogynon was taken off the market in 1981 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation